2020
DOI: 10.4049/jimmunol.1901167
|View full text |Cite
|
Sign up to set email alerts
|

TCR Signal Strength and Antigen Affinity Regulate CD8+ Memory T Cells

Abstract: CD8+ T cells play a critical role in adaptive immunity, differentiating into CD8+ memory T cells that form the basis of protective cellular immunity. Vaccine efficacy is attributed to long-term protective immunity, and understanding the parameters that regulate development of CD8+ T cells is critical to the design of T cell–mediated vaccines. We show in this study using mouse models that two distinct parameters, TCR signal strength (regulated by the tyrosine kinase ITK) and Ag affinity, play important but sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…The surprising finding that the absence of ITK does not affect the ability of SR exposure to generate an IL17A/Th17 response suggests that there are signals received by these cells in vivo, that may overcome the defect observed in vitro or under other conditions in vivo. ITK regulates the strength of the signal from the TcR 17 , 32 , and so we evaluated whether Itk −/− T cells receive adequate TcR signals in vivo during exposure to SR by utilizing Nur77-GFP mice 33 . We first examined the strength of TcR signals received by Itk −/− T cells in vivo by examining Nurr77 expression in T cells from non-exposed mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surprising finding that the absence of ITK does not affect the ability of SR exposure to generate an IL17A/Th17 response suggests that there are signals received by these cells in vivo, that may overcome the defect observed in vitro or under other conditions in vivo. ITK regulates the strength of the signal from the TcR 17 , 32 , and so we evaluated whether Itk −/− T cells receive adequate TcR signals in vivo during exposure to SR by utilizing Nur77-GFP mice 33 . We first examined the strength of TcR signals received by Itk −/− T cells in vivo by examining Nurr77 expression in T cells from non-exposed mice.…”
Section: Resultsmentioning
confidence: 99%
“…ITK plays an important role as an amplifier of the TCR signals, and in humans, and/or mouse models, has been shown to regulate the development of both CD4 + and CD8 + T-cells in the thymus, and influences the development of specific populations of γδ T cells, i NKT cells, and intestinal Innate Lymphoid Cell 2 populations 10 16 . In the periphery, the signals regulated by ITK are able to tune the development of CD8 + T cell memory cells 17 , as well as the differentiation of CD4 + effector T cells 18 23 . A specific role for ITK in the development of Th17 cells has been demonstrated in both mouse models 24 , and in human T cells 11 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies mainly looked at central and effector memory differentiation and found that weak TCR signals specifically favor central memory development via expression of high levels of Eomes. Moreover, TCR signal strength inversely regulated the input of inflammation by controlling the expression of inflammatory cytokine receptors and enabling a higher frequency of CD8 T cells that have been stimulated by weak antigens to become central memory T cells ( 1 , 133 ). In the case of resident memory differentiation, the role of TCR signaling has been largely overlooked until recently.…”
Section: T Cell Receptor Signals and Resident Memory Cd8 T Cellsmentioning
confidence: 99%
“…Among the signaling cascades the engaged TCR can trigger, the ones able to provide a digital type of signaling, such as Itk/Calcium and ERK (which regulate transcription factors, IRF4 and AP-1 family members) seem to be preferentially involved in promoting terminal effector differentiation ( 133 , 135 , 136 ). Their role in CD8 T RM remains unknown.…”
Section: T Cell Receptor Signals and Resident Memory Cd8 T Cellsmentioning
confidence: 99%
“…The sensing of these cytokines, however, cannot be interpreted separately from cognate Ag. Indeed, reduced TCR signal strength resulted in increased MP accumulation even in the presence of inflammatory cytokines (3). The effect of inflammation on MP cells may also be context-dependent.…”
Section: How Inflammation Shapes Memory Cd8 1 T Cell Generationmentioning
confidence: 99%